COP29: Multilateralism, Delays, Controversies, and Mixed Results for Climate Finance, Adaptation, and Agriculture - Miranda, Daniela (2024)
Reflections from COP29 by Daniela Miranda, Advocacy, Negotiations, and Partnership Intelligence, CGIAR on the results from key negotiation tracks for the agriculture and food systems sector.